Criminal Law Analysis of the Modus Operandi of Illegal Cigarette Smuggling: a Case Study in Batam City - Riza, Khairul; Lubis, Irpan Husein (Kajian Ilmiah Hukum dan Kenegaraan, 2025)
Purpose: This study aims to analyze the criminal law aspects and modus operandi of illegal cigarette smuggling in Batam City, as well as to assess the effectiveness of law enforcement based on the applicable legal regulations in Indonesia. Methodology/approach: The research uses a normative juridical method with a statutory and case approach, supported by primary data collected through interviews with law enforcement officials and secondary data from relevant legal documents and literature. Results/findings: The findings reveal that illegal cigarette smuggling in Batam is carried out through non-official sea routes using high-speed boats, falsification of customs documents, and well-organized distribution networks. Despite existing laws such as Law No. 39 of 2007 on Excise and Law No. 17 of 2006 on Customs, enforcement remains weak due to limited surveillance and involvement of corrupt individuals. Limitations: This study is limited to the case of Batam City and does not cover other regions facing similar smuggling issues. Contribution: The research provides a legal analysis and practical recommendations for strengthening enforcement mechanisms and regulatory reforms in combating smuggling crimes. The novelty of this research lies in the systematic mapping of the patterns of illegal cigarette smuggling networks in Batam, which is examined integrally through the perspective of criminal law and a law enforcement approach based on national regulations.